Comparison of the extent and pattern of cognitive impairment among predialysis, dialysis and transplant patients: A cross‐sectional study from Australia. Issue 11 (17th October 2017) - Lambert, Kelly; Mullan, Judy; Mansfield, Kylie; Lonergan, Maureen
Abstract: Aim: The aim of this study was to compare the extent of cogntive impairment and the types of cognitive deficits in an Australian cohort of four patient groups with end stage kidney disease. Characteristics predicting the presence of cognitive impairment were also evaluated. Methods: Observational cross‐sectional study of 155 patients with end stage kidney disease are recruited from a regional Australian renal unit. Eligible participants included those whose estimated Glomerular Filtration Rate was < 30 ml/min per 1.73 m 2, were undertaking peritoneal or haemodialysis, or had received a kidney transplant. The Montreal Cognitive Assessment tool was used to screen the study participants for cognitive impairment and evaluate cognitive deficits. Cognitive impairment was defined as a total Montreal Cognitive Assessment tool score ≤24/30. Results: The extent of cognitive impairment varied between the four groups with end stage kidney disease. Factors predicting the presence of cognitive impairment included undertaking dialysis, age ≥65, male gender and the presence of diabetes or cerebrovascular disease. Deficits in executive function, attention, language, visuospatial skills, memory and orientation were common among the study participants, and the extent of these deficits varied between groups. Limitations to the study included the cross‐sectional design, and that the presence of confounders like depression were not recorded. Conclusion: The impact of disparities in the cognitive capabilities identified in this study are likely to be far reaching. Tailoring of education and self‐management programmes to the cognitive deficits of individuals is required. Summary at a Glance: Authors showed the impact of disparities in the cognitive capabilities are likely to be far reaching. Tailoring of education and self‐management programs to the cognitive deficits of individuals is really required. The topic of this paper would be helpful to the readers who are taking care of elderly dialysis patients.